2007
DOI: 10.1113/jphysiol.2007.128736
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the response of the iliac artery to wall shear stress in the anaesthetized pig

Abstract: The functional significance of shear stress-induced vasodilatation in large conduit arteries is unclear since changes in the diameter have little effect on the resistance to blood flow. However, changes in diameter have a relatively large effect on wall shear stress which suggests that the function of flow-mediated dilatation is to reduce wall shear stress. The mean and pulsatile components of shear stress vary widely throughout the arterial system and areas of low mean and high amplitude of wall shear stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 38 publications
(52 reference statements)
5
37
0
Order By: Relevance
“…These findings were in line with Miyakawa et al, who undertook experiments under venous and arterial hemodynamic conditions for one, two, and four days [16]. Similar observations were made by Kelly et al, who investigated the shear stress of iliac arteries in anaesthetized pigs [4]. Increases of diameter and wall shear stress were accompanied by an increase of flow in arteries.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These findings were in line with Miyakawa et al, who undertook experiments under venous and arterial hemodynamic conditions for one, two, and four days [16]. Similar observations were made by Kelly et al, who investigated the shear stress of iliac arteries in anaesthetized pigs [4]. Increases of diameter and wall shear stress were accompanied by an increase of flow in arteries.…”
Section: Discussionsupporting
confidence: 76%
“…However, in vivo experiments, performed mainly in animal models, may not directly reflect the changes in the human body, while clinical studies could raise ethical issues. On the contrary, ex vivo experiments have less limitations as they may be performed on tissues or on primary cells [3,4]. In addition, recent biomedical research is directing the delivery of cells with biomaterials for the therapeutic advancement and regeneration of tissues [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] This response is completely abolished with nitric oxide inhibition following application of N G -nitro-L-arginine methyl ester. 20) In human brachial artery Doshi, et al found that the FMD response was almost fully blocked using N G -monomethyl-L-arginine. 21) Thus, NO bioavailability is the most important factor of FMD.…”
Section: Discussionmentioning
confidence: 99%
“…This function depends on the endothelial cells producing nitric oxide (NO) [4], which relax the smooth muscle of the arterial wall, and thus increase the lumen diameter [5]. The NO is rapidly removed by haemoglobin, as its accumulation would be toxic.…”
Section: The Importance Of Flow Mediated Arterial Dilatation (Fmd)mentioning
confidence: 99%